Can Culturally Specific Perspectives to Teaching Western Classical Music Benefit International Students? A Call to Re-examine “What the Teacher Does” - Ford, Biranda (Frontiers in Education, 2020)
Institutions that teach Western classical music in higher education in the West have been increasingly reliant on international students from Asia, particularly China to fulfil recruitment targets. This article examines research in music performance tuition and the general higher education literature on pedagogy for international students. After demonstrating that Asian musicians feel the presence of a covert racial and cultural prejudice caused by assimilationist values in both Western classical music and in higher education, it reviews various approaches to teaching international students in higher education and brings this into dialogue with research on music performance pedagogy. Identifying various pitfalls of attempting to promote a greater awareness of students from different backgrounds, such as stereotyping and the indiscriminate use of racialized discourses, it argues nonetheless that a greater sensitivity to cultural difference is needed in music performance tuition. By reconsidering through an intercultural lens what teachers currently do and their beliefs about music and teaching that they transmit to their students, music education research can play an important role in breaking down assimilationist attitudes to the performance and teaching of Western classical music.